Assessing seropositivity for IgG antibodies against SARS-CoV-2 in Ahmedabad city of India: a cross-sectional study. Issue 1 (5th January 2021) - Prakash, Om; Solanki, Bhavin; Sheth, Jay K; Joshi, Bhavin; Kadam, Mina; Vyas, Sheetal; Shukla, Aparajita; Tiwari, Hemant; Rathod, Sanjay; Rajput, Anil; Trivedi, Toral; Ramanuj, Vaibhav; et al.
Abstract : Objectives: To study the percentage seropositivity for SARS-CoV-2 to understand the pandemic status and predict the future situations in Ahmedabad. Study design: Cross-sectional study. Settings: Field area of Ahmedabad Municipal Corporation. Participants: More than 30 000 individuals irrespective of their age, sex, acute/past COVID-19 infection participated in the serosurvey which covered all the 75 Urban Primary Health Centres (UPHCs) across 48 wards and 7 zones of the city. Study also involved healthcare workers (HCWs) from COVID-19/non-COVID-19 hospitals. Interventions: Seropositivity of IgG antibodies against SARS-CoV-2 was measured as a mark of COVID-19 infection. Primary and secondary outcomes: Seropositivity was used to calculate cumulative incidence. Correlation of seropositivity with available demographic detail was used for valid and precise assessment of the pandemic situation. Results: From 30 054 samples, the results were available for 29 891 samples and the crude seropositivity is 17.61%. For all the various age groups, the seropositivity calculated between 15% and 20%. The difference in seropositivity for both the sex group is statistically not significant. The seropositivity is significantly lower (13.64%) for HCWs as compared with non-HCWs (18.71%). Seropositivity shows increasing trend with time. Zone with maximum initial cases has high positivity as compared with other zones. UPHCs with recent rise in cases are leading in seropositivity as compared with earlier and widely affected UPHCs. Conclusions: The results of serosurveillance suggest that the population of Ahmedabad is still largely susceptible. People still need to follow preventive measures to protect themselves till an effective vaccine is available to the people at large. The data indicate the possibility of vanishing immunity over time and need further research to cross verify with scientific evidences.